Differentiation Strategies in a Multicultural Classroom: A Case Study in an Elementary School - Arisman Sabir; Yuanyuan Wang; Guijiao Zou (Yayasan Adra Karima Hubbi, 2024)
The increasing cultural diversity in classrooms presents both challenges and opportunities for educators in delivering effective instruction. Differentiation strategies have emerged as a vital pedagogical approach to address the varying learning needs, cultural backgrounds, and language proficiencies of students in multicultural classrooms. This study explores the use of differentiation strategies in a multicultural elementary school and analyzes their effectiveness in promoting student engagement, academic performance, and social inclusion. A qualitative case study approach was used to gain a deeper understanding of differentiation practices. Data were gathered through classroom observations, semi-structured interviews with teachers, and focus group discussions with students. The findings revealed that differentiation strategies, such as flexible grouping, customized instructional materials, and culturally relevant content, significantly improved student engagement and participation. However, teachers encountered challenges in managing diverse learning needs and adapting instruction to meet the requirements of the standardized curriculum. Despite these challenges, differentiated instruction helped create a more inclusive learning environment, supporting academic growth and social integration among students from various cultural backgrounds.